SPEAKING SUCCESS: A CURRENT PERSPECTIVE ON LANGUAGE’S IMPACT IN MARKETING AND SERVICES - Carter, Olivia A (International Journal of Allied Research in Marketing and Management (IJARMM), 2023)
This paper delves into the significance of words in the realm of marketing, both as tools of communication and as instruments that shape the practice of marketing. With a focus on marketing terms and concepts, the discussion oscillates between general marketing and service-specific perspectives, as well as practitioner and academic viewpoints. The pivotal role of words in understanding customers, facilitating transactions, and engaging with the marketplace is acknowledged. The paper highlights the escalating phenomenon of vocabulary creep in marketing and its implications, substantiated by data gleaned from marketing practitioners and services marketing textbooks. The author then offers remedies for managing vocabulary creep. Additionally, the paper explores the consumer’s stance on marketing terminology, further enriching the discourse. By delving into the intersections of linguistic nuance and marketing practice, this work contributes to the understanding of how language shapes the dynamics of marketing and service domains.